Apoptosis, Senescence and Cancer - Gewirtz, David A.; Holt, Shawn E.; Grant, Steven (Cancer Drug Discovery and Development, 2007)
Apoptosis, Senescence and Cancer provides insight into established practices and research into apoptosis and senescence by thoroughly examining novel and emerging techniques and research in the fields of cell death pathways, senescence growth arrest, drugs and resistance, DNA damage response, and other topics which still hold mysteries for researchers. The volume is divided into six easy to follow sections. The first is Apoptosis and Alternative Modes of Cell Death, followed by chapters on Telomeres and Telomerase, Senescence, Genomic Instability and Tumorigenesis. The third part covers DNA Damage Response, Signaling Pathways and Tumorigenesis, while the fourth delves into Resistance and Sensitization. The book concludes with Established Cancer Therapies and a section which looks toward the future with Recent and Developing Cancer Therapies. In total, this volume provides basic scientists and clinicians with a deeper and more complete understanding of the cellular responses of malignancies which may determine the effectiveness of treatment, both in the initial stages of the disease as well as in disease recurrence.